Late Metastatic Melanoma after 25 Years: A Case Report and a Brief Literature Review - Elena Pescarini; Gabriela Spanikova; Zacharia Mbaidjol; Eleonora De Antoni; Vincenzo Vindigni; Franco Bassetto (Case Reports in Surgery)
The incidence of cutaneous malignant melanoma has shown a drastic increase over recent decades, and approximately 70% of newly diagnosed melanoma are tumors with a Breslow thickness less or equal to 1 mm. In the literature, there are well-documented rare cases of late metastasis of thin melanoma, and given their growing incidence, it is expected in the future to see more cases of late recurrence. We present a case report of a metastatic cutaneous melanoma 25 years from diagnosis and a review of the literature. A 61-year-old female patient presented with a newly discovered asymptomatic nodule on her thigh. Her relevant past medical history included a completely excided lesion with Breslow 1.4 mm thickness in 1989 for which she was followed up according to the guidelines and subsequently declared cured after 10 years of surveillance. Fine-needle aspiration and cytological analysis of the lesion proved to be a subcutaneous localization of malignant melanoma. The lesion was completely excised, and the patient has remained disease free since her surgery. The aim of this case report is to emphasize that late metastasis remains uncommon but a definitive cure from melanoma cannot always be considered a disease-free interval of 10 years. Physicians should always be aware of previous melanoma diagnosis with newly discovered suspicious lesions. Better patient education could improve the detection of recurrence and secondary melanomas without any need for more frequent follow-up visits and a prolonged follow-up time.